STUDY OF PETROLOGY AND MINERALOGY OF KIE BESI VOLCANIC ROCKS IN SOUTHERN HALMAHERA, NORTH MALUKU PROVINCE - PRIMA, DESWANDANA
Research area administratively located on the Makian Island, Southern Halmahera, North Maluku Province. Geographically, Kie Besi Volcano lies at 0º 19’ N dan 127º 24' E with 1357 MASL height. Kie Besi Volcano is a stratovolcano that has one main crater with around 1500 m x 1400 m dimension. Magmatic process and evolution during the formation of volcanic rocks can be represented by mineralogy, evolution of mineral composition, and plagioclase micro texture. Temperature of magma formation could be determined from the presence of coexisting pyroxene. This research applies method of petrology and mineralogy analysis on olivine, pyroxene, plagioclase, hornblende, and opaque mineral from Kie Besi volcanic rocks. The samples come from three rock units, from older to younger: Lava Malapa (LMp) and Lava Powate (LP) representing pre-1988 eruption and Lava Kie Besi (KlKb) representing 1988 eruption. The lithology of Lava Malapa unit is pyroxene andesite with flow texture while Lava Powate unit is olivine basalt with intersertal texture, and Kubah Lava Kie Besi unit is pyroxene andesite and olivine-bearing andesite with minor flow texture in both. All samples show vesicular structures. The magma of Kie Besi Volcano has a calc-alkaline affinity. The evolution of Kie Besi Volcano magma began with the formation of Lava Malapa unit by basaltic-andesitic magma with temperature of 9500C – 10250C. This unit-forming basaltic-andesitic magma was influenced by convection, basaltic magmatic injection, and adiabatic decompression as magma moved from magma chamber to the surface which was eventually terminated by undercooling process. The basaltic magma injection was progressively intensified followed by magma mixing made more basaltic magma and magma chamber rose to 11000C – 11750C formed Lava Powate unit. Magmatic process in the magma chamber during the formation of Lava Powate unit is strongly influenced by basaltic magma injection process that makes the heating and dissolution process run more intensively with adiabatic decompression and convection as the magma moves to the surface and terminated by undercooling process. Furthermore, there was a decrease in temperature in the magma chamber produces basalticandesitic magma with temperature of 9500C – 10750C and formed Kubah Lava Kie Besi unit. The magma chamber at that time was strongly influenced by the convection process, basaltic magma injection, adiabatic decompression, and terminated by the undercooling process.